2022
DOI: 10.1111/codi.16289
|View full text |Cite
|
Sign up to set email alerts
|

Physicians perceive that ostomates have decreased quality of life but not overall health: An international survey of physicians

Abstract: Aim The aim of this work was to evaluate physicians' perceptions of ostomates' quality of life (QoL) and comfort of care among an international sample of physicians caring for ostomates. Method This was a cross‐sectional survey study. We conducted a survey of primary care physicians (PCP), gastroenterologists (GI), and general surgeons (GS) from three continents using the SERMO online physician platform. We piloted the survey for content, clarity and domain development using a pilot sample of physicians from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…This study supports and expands previous work that has found that navigating healthcare can be an additional stressor for people with ostomies 11. Respondents reported both successes and challenges, and discussed healthcare encounters that were with ostomy experts as well as with clinicians who were unfamiliar with ostomies.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study supports and expands previous work that has found that navigating healthcare can be an additional stressor for people with ostomies 11. Respondents reported both successes and challenges, and discussed healthcare encounters that were with ostomy experts as well as with clinicians who were unfamiliar with ostomies.…”
Section: Discussionsupporting
confidence: 84%
“…This study supports and expands previous work that has found that navigating healthcare can be an additional stressor for people with ostomies. 11 Respondents reported both successes and challenges, and discussed healthcare encounters that were with ostomy experts as well as with clinicians who were unfamiliar with ostomies. When describing successes in communication, participants recalled when clinicians dedicated time to educate them about their ostomy, including giving them thorough guidance on life with an ostomy, trialling creative solutions for their ostomy care, and providing the patients with hands-on training to reduce uncertainty about caring for their ostomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Additionally, HCPs have expressed difficulties in knowing when the right time to begin discussions about ostomies may be and which HCP may be ideal to lead these discussions 8 -does the gastroenterologist (GI) lead the discussion as the patient's primary HCP or defer to the surgeon? Ostomy-related stigma for HCPs remains pervasive, [18][19][20][21][22] including perceptions by HCPs that people living with ostomies have lower quality of life, 23 though there is limited scientific understanding of how HCPs perceive ostomy-related stigma for themselves and their receptions of ostomy-related stigma for patients and families; understanding ostomy-related stigma from HCPs' perspectives would represent a critical opportunity to directly tackle and work to reduce stigma for this surgery and support neutral and calm conversations about complex care decisions.…”
mentioning
confidence: 99%